Identification of Heat-Responsive Genes in Guar [Cyamopsis tetragonoloba (L.) Taub] - Aref Alshameri; Fahad Al-Qurainy; Abdel-Rhman Gaafar; Salim Khan; Mohammad Nadeem; Saleh Alansi (International Journal of Genomics)
The threat of heat stress on crop production increased dramatically due to global warming leading to the rise on the demand of heat-tolerant crops and understanding their tolerance. The leguminous forage crop Guar [Cyamopsis tetragonoloba (L.) Taub] is a high-temperature tolerant plant with numerous works on its tolerance at morph-physiological levels but lack on molecular thermotolerance level. In the current study, the differential gene expression and the underlying metabolic pathways induced by heat treatment were investigated. An RNA-Seq study on Guar leaves was carried out to estimate gene abundance and identify genes involved in heat tolerance to better understand the response mechanisms to heat stress. The results uncovered 1551 up- and 1466 downregulated genes, from which 200 and 72 genes with unknown function could be considered as new genes specific to guar. The upregulated unigenes were associated with 158 enzymes and 102 KEGG pathways. Blast2GO, InterProScan, and Kyoto Encyclopaedia of Genes and Genomes packages were utilized to search the functional annotation, protein analysis, enzymes, and metabolic pathways and revealed hormone signal transduction were enriched during heat stress tolerance. A total of 301 protein families, 551 domains, 15 repeats, and 3 sites were upregulated and matched to those unigenes. A batch of heat-regulated transcription factor transcripts were identified using the PlantTFDB database, which may play roles in heat response in Guar. Interestingly, several heat shock protein families were expressed in response to exposure to stressful conditions for instance small HSP20, heat shock transcription factor family, heat shock protein Hsp90 family, and heat shock protein 70 family. Our results revealed the expressional changes associated with heat tolerance and identified potential key genes in the regulation of this process. These results will provide a good start to dissect the molecular behaviour of plants induced by heat stress and could identify the key genes in stress response for marker-assisted selection in Guar and reveal their roles in stress adaptation in plants.